Thicker than water ebook A memoir. - Washington, Kerry (2023)
Award-winning actor, director, producer, and activist Kerry Washington shares the deeply moving journey of her life so far, and the "beautiful" story of discovering her truth in this instant New York Times bestseller (Oprah Winfrey). While on a drive in Los Angeles, on a seemingly average afternoon, Kerry Washington received a text message that would send her on a life-changing journey of self-discovery. In an instant, her very identity was torn apart, with everything she thought she knew about herself thrown into question.   In Thicker than Water , Washington gives readers an intimate view into both her public and private worlds—as a mother, daughter, wife, artist, advocate, and trailblazer. Chronicling her upbringing and life’s journey thus far, she reveals how she faced a series of challenges and setbacks, effectively hid childhood traumas, met extraordinary mentors, managed to grow her career, and crossed the threshold into stardom and political advocacy, ultimately discovering her truest self and, with it, a deeper sense of belonging.   Throughout this profoundly moving and beautifully written memoir, Washington attempts to answer the questions so many have struggled with: Who am I? What is my truest and most authentic self? How do I find a deeper sense of connection and belonging? With grace and honesty, she inspires readers to search for—and find—themselves.